A death in Malta : an assassination and a family's quest for justice - Caruana Galizia, Paul, 1988- (Riverhead Books, 2023)
"A journalist's spellbinding account of the shocking murder of his muckraking mother and a quest for justice that has reverberated far beyond their tiny homeland"--